2013
DOI: 10.12932/ap0264.31.2.2013
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors of patient compliance in allergic rhinitis

Abstract: Compliance with intake of sublingual immunotherapy and H1-antihistamines is high. However, our findings point out that patients with characteristics such as a comorbid bronchial asthma or mild symptoms have higher odds for noncompliance and require attentive monitoring to reduce healthcare costs and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
4
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
3
4
1
6
Order By: Relevance
“…data are in agreement with several previously published studies of patients with PAR, which have reported the rates of around 70-80%[10,15,[17][18][19][20][21][22]. Another study has reported a higher compliance of approximately 97%[20].However, in that study, the patients counted the pills themselves and reported via a Variations caused by the method of compliance measurement were apparent in our study.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…data are in agreement with several previously published studies of patients with PAR, which have reported the rates of around 70-80%[10,15,[17][18][19][20][21][22]. Another study has reported a higher compliance of approximately 97%[20].However, in that study, the patients counted the pills themselves and reported via a Variations caused by the method of compliance measurement were apparent in our study.…”
supporting
confidence: 93%
“…The available data on the patient adherence to allergen-specific immunotherapy are often conflicting [11,12]. In particular, in allergic rhinitis, compliance rates for sublingual administration range between 70% and 97% [10,[13][14][15][16][17][18][19][20][21][22]. This wide variation might be explained by differences in the characteristics and methodology of the studies, such as the population profiles and the definition of compliance [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Не-смотря на то что обострение АР не приводит к смер-тельному исходу, он может стать причиной развития АК и БА. В США затраты на лечение АР с 2000 по 2005 г. возросли с 6,1 до 11,2 млрд долларов [5].…”
unclassified